Study of Vibration on Ballasted and Non-Ballasted Railway Steel Bridge - Azahari, Adib Saifullah (Progress in Engineering Application and Technology, 2023)
Interaction of running wheels and rails on the railway steel bridge will produce vibration. However, too much vibration produced from dynamic movement of train along the railway steel bridge can cause a problem to the safety of the bridge itself. In Keretapi Tanah Melayu Berhad (KTMB), there are two types of tracks on railway steel bridge which are ballasted track and non-ballasted track that can give different values of vibration to the structure of railway steel bridge. So, in order to define the value of vibration on both railway steel bridges, a vibration test plan will be conducted by using a 4-channel portable sound and vibration analyzer. The vibration test plan also can spot the highest vibration produced along the railway steel bridge by comparing the peak of vertical acceleration of each sample data. Thus, the highest value of vibration in terms of vertical acceleration is at the approach point of non-ballasted railway steel bridge and the ballasted tracks is proven to be able to absorb more vibration and become more cost-effective in terms of maintenance.